PLC based Multi-Floor Elevator Control System - Shrey Gupta (Institute of Advanced Engineering and Science, 2015)
This paper presents programmable logic controller based elevator control system. Primary focus is on using programmable logic controller to build the elevator model. To control the motion of the elevator through various levels DC geared motor is used. Push buttons are used to give signal to the elevator to come to the desired floor, traversing up and down. Moreover DC relays are used as switches, not protective devices, to drive the motor in clockwise and anticlockwise direction. Ladder logic is used for the model implementation.